Celastrol in cancer therapy: Recent developments, challenges and prospects. (28th November 2021) - Lim, Hannah Ying; Ong, Pei Shi; Wang, Lingzhi; Goel, Arul; Ding, Lingwen; Li-Ann Wong, Andrea; Ho, Paul Chi-lui; Sethi, Gautam; Xiang, Xiaoqiang; Goh, Boon Cher
Abstract: Cancer is one of the world's biggest healthcare burdens and despite the current advancements made in treatment plans, the outcomes for oncology patients have yet to reach their full potential. Hence, there is a pressing need to develop novel anti-cancer drugs. A popular drug class for research are natural compounds, due to their multi-targeting potential and enhanced safety profile. One such promising natural bioactive compound derived from a vine, Tripterygium wilfordii is celastrol. Pre-clinical studies revolving around the use of celastrol have revealed positive pharmacological activities in various types of cancers, thus suggesting the chemical's potential anti-cancerous effects. However, despite the numerous preclinical studies carried out over the past few decades, celastrol has not reached human trials for cancer. In this review, we summarize the mechanisms and therapeutic potentials of celastrol in treatment for different types of cancer. Subsequently, we also explore the possible reasons hindering its development for human use as cancer therapy, like its narrow therapeutic window and poor pharmacokinetic properties. Additionally, after critically analysing both in vitro and in vivo evidence, we discuss about the key pathways effected by celastrol and the suitable types of cancer that can be targeted by the natural drug, thus giving insight into future directions that can be taken, such as in-depth analysis and research of the druggability of celastrol derivatives, to aid the clinical translation of this promising anti-cancer lead compound. Highlights: Celastrol identified as a potential drug for cancer therapy. Narrow therapeutic window as crucial factor for its further development. Novel formulations needed to improve bioavailability and reduce toxicity. New analogues for increasing the anticancer activity of celastrol.